2011
DOI: 10.1007/s11096-010-9470-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring community pharmacists’ views on generic medicines: a nationwide study from Malaysia

Abstract: The Malaysian pharmacists' have lack of information and/or trust in the generic manufacturing and/or approval system in Malaysia. This issue should be addressed by pharmacy educators and relevant government agencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 20 publications
1
43
4
Order By: Relevance
“…In contrast to other reports of reticent pharmacist views, 3,8,9 this study has shown that Irish pharmacists were generally positive towards, and accepting of, generic medicines, with many holding the view that they are as effective as the originator, with the exception of nonsubstitutable situations-such as with Narrow Therapeutic Index drugs-and that differences in presentation can be a source of problems for some patients. Very few pharmacists expressed reticent opinions, but 1 of the primary concerns, as has been reported elsewhere, 6 was that confusion caused by differing aesthetic presentations of generic medicines has the potential to be problematic for patients.…”
Section: ■■ Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to other reports of reticent pharmacist views, 3,8,9 this study has shown that Irish pharmacists were generally positive towards, and accepting of, generic medicines, with many holding the view that they are as effective as the originator, with the exception of nonsubstitutable situations-such as with Narrow Therapeutic Index drugs-and that differences in presentation can be a source of problems for some patients. Very few pharmacists expressed reticent opinions, but 1 of the primary concerns, as has been reported elsewhere, 6 was that confusion caused by differing aesthetic presentations of generic medicines has the potential to be problematic for patients.…”
Section: ■■ Discussioncontrasting
confidence: 99%
“…Internationally, a limited number of assessments have taken place for such countries as New Zealand, 9 Portugal, 4 South Africa, 5 Malaysia, 8 France, 10 and Sweden 6 that included studies on views held regarding specific medication types, such as antiepileptic drugs 7 and inhalers. 3 Given the major changes currently underway in the Irish health care system (i.e., the introduction for the first time of reference pricing and generic substitution), the opinions and behaviors of this critical stakeholder group have the potential to be pivotal to the success or failure of the changes being implemented.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of this kind, we demonstrated that generic prescribing by both consultants and general practi-tioners in the United Arab Emirates was far from ideal [2]. However, there is evidence that not only doctors but also pharmacists hold negative views of generics and resist prescribing generic medicines [3] [4]. Patients have been shown to have poor knowledge and misconceptions about generic medicines [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Malaysia, it was reported that customers showed a high degree of mistrust when the manufacturer was unknown and deemed it difficult to explain that a drug with a different shape and colour can have the same efficacy as the drug previously used 28 . While in a Swedish study pharmacists felt that a reason for the mistrust could be that generics might have different tablet coating, lack calendar packaging, and not always be packed in ""the same exclusive way"" as the brand products 29 .…”
Section: Pharmacists' Behaviour Towards Generic Drugsmentioning
confidence: 99%